(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the ways of formation of student’s cross-cultural communication, as nowadays information technologies including electronic textbooks are widely used in an educational process. The advantages and interactivity of foreign and domestic e-books usage in mastering of professional education for the following disciplines: «Foreign language (professional)», «Practical course of a foreign language», «Professionally-oriented foreign language» are revealed. Foreign language e-books are considered as the newest type of educational aids, requiring elaboration of theoretical and practical issues of creation. The importance of electronic textbook is considered as the newest type of training books in developing. Teaching with the help of electronic textbooks increases the quality of study, meets the demands of modern education and forms student’s necessary competences.